Australian Video Viewing Survey: Household Consumption across Formats - Kennedy, David (Journal of Telecommunications and the Digital Economy, 2021)
In late 2020, Venture Insights conducted a video consumer survey of 1,003 Australian households. This paper provides an overview of the results. A television set remains the most common device for watching video, but a substantial majority of households also watch video on PCs, tablets and smartphones. Internet-connected TVs are now common. Only 24% of households currently have a 4K or better TV, but 44% of households anticipate buying a 4K TV set over the next three years. More than half of households do not subscribe to a pay-TV service. Of those which do, two-thirds have Foxtel. Netflix remains dominant in the Australian subscription video market, while its main competitors are each subscribed to by about one-fifth of households. Most survey respondents expect their video consumption to remain stable across all formats over the next year.